2018
DOI: 10.1242/bio.032631
|View full text |Cite
|
Sign up to set email alerts
|

TheStk35locus contributes to normal gametogenesis and encodes a lncRNA responsive to oxidative stress

Abstract: Serine/threonine kinase 35 (STK35) is a recently identified human kinase with an autophosphorylation function, linked functionally to actin stress fibers, cell cycle progression and survival. STK35 has previously been shown to be highly expressed in human testis, and we demonstrated its regulation by nuclear-localized importin α2 in HeLa cells. The present study identifies progressive expression from the STK35 locus of two coding mRNA isoforms and one long non-coding RNA (lncRNA) in mouse testis during spermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…By ranking the top 15 nodes in our ceRNA network by degree centrality, we identified a range of significant ceRNA interactions in CAD (see Table 2); these findings concurred with previous literature (see Table 4) (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). It was evident from our results that several ceRNAs were related to cardiovascular diseases.…”
Section: Stk35supporting
confidence: 90%
See 2 more Smart Citations
“…By ranking the top 15 nodes in our ceRNA network by degree centrality, we identified a range of significant ceRNA interactions in CAD (see Table 2); these findings concurred with previous literature (see Table 4) (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). It was evident from our results that several ceRNAs were related to cardiovascular diseases.…”
Section: Stk35supporting
confidence: 90%
“…STK35 may act as a central kinase linking the actin stress fibers, cell cycle progression, migration of endothelial cells, and survival. Its protein constitutive overexpression enhances caspase-independent cell death under oxidative stress conditions (44)(45)(46) NA indicates no data available. BMP2, bone morphogenetic protein 2; ceRNA, competitive endogenous RNA; KLF12, Krüppel like factor 12; NACC2, nucleus accumbens associated 2; PSMA3, proteasome subunit alpha type-3; STK35, serine/threonine kinase 35.…”
Section: Stk35mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in endothelial cells, the silencing of the STK35L1gene drastically impaired cell migration 9 . A study showed that importin-a2 enhanced the expression of the stk35l1gene, and constitutive overexpression of STK35L1 activates caspase-independent cell death under oxidative stress conditions 10 .STK35 (STK35L1) knockout mice showed defects in eye development and were infertile 11 . STK35L1 transcript was altered in colorectal cancer and cardiomyopathy 12,13 .…”
Section: Introductionmentioning
confidence: 99%